Hubungan Fraud Terhadap Financial Statement di Indonesia (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Dyah Ayu Pitaloka, Riyani Titian; Mertha Agung Durya, Ngurah Pandji (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study uses a quantitative approach that aims to examine and analyze the relationship between fraud and financial statements by using the fraud diamond theory as measured by fraud scores in energy sector companies. The data used in this study comes from secondary data, which is obtained by accessing financial reports on the IDX website. Data analysis techniques are applied to the logistic regression analysis by operating SPSS 26 software. The findings of this study indicate that the nature of industry has an effect on financial statement fraud. However, personal financial need, auditor firm size, and change of auditor have no effect on financial statement fraud.